Determination of the dynamic load factors for crowd jumping using motion capture technique - Li, Guo; Ji, Tianjian; Chen, Jun (Engineering structures, 2018)
•An experiment of crowd jumping was conducted using a 3D motion capture technique.•Dynamic load factor ratios were proposed and calculated using the Monte Carlo method.•Dynamic load factor ratios against crowd sizes tend to be a constant for large crowd.•Crowd jumping load model was developed which has some advantages than other models. The effect of imperfect synchronization is a key factor for modeling crowd jumping loads. Knowledge on this effect is limited due to the lack of crowd jumping experiments. This paper presents an experimental study of crowd jumping of 48 subjects at a frequency range between 1.5 Hz and 3.5 Hz with an interval of 0.1 Hz. The jumping movements of all participants were synchronously and simultaneously monitored using a three-dimensional (3D) motion capture technique. Based on the measured data, dynamic load factors (DLFs) against crowd sizes were determined using the Monte Carlo method. Then, they were converted to the DLF ratios to reduce numerical errors. Results show that the DLF ratios tend to be a constant for a crowd over 48. A simple expression of the ratios is provided using curve fitting. Then the crowd jumping load model was summarized and compared with the measured and published results. Finally, limitations of this study were discussed.